Triangle group associated with generalized modular equation - Alam, Md Shafiul; Saha, Bijan Krishna (Journal of Bangladesh Academy of Sciences, 2024)
Detailed abstract is in the PDF file. J. Bangladesh Acad. Sci. 48(2); 207-215: December 2024